INTERNALISASI NILAI KEDISIPLINAN MELALUI PEMBIASAAN TADARUS AL-QUR’AN DI MA PLUS DARUL HUDA KLEPU SUMBERMANJING WETAN KAB. MALANG - Saadatul Maulidiah; Anwar Sadullah; Dzulfikar Rodafi (VICRATINA, 2022)
Discipline is the basis of success therefore discipline must be instilled early on in a person, especially in students. This research was carried out at MA Plus Darul Huda Klepu Sumbermanjing wetan Kab. Malang. This research uses a qualitative approach with the type of case study. Data collection methods used are observation, interviews and documentation. Data analysis techniques and checking the validity of data and data are presented in descriptive form. The results showed that: 1). Discipline of students includes discipline of time, discipline of study, discipline of dress and discipline in worship. 2). The implementation of the habituation of tadarus Al-Qur'an is carried out every day before starting teaching and learning activities. 3). Supporting and inhibiting factors in internalizing the value of discipline through habituation of tadarus Al-Qur'an.